Intelligent tourism systems for smart travel recommendation - Tan, Jessileen Li Ting (2014)
In this project, it aims is to provide users with smart travelling recommendations such that it will be easier for users to obtain travel information. Therefore, this project comprises of 2 demo systems, the web-based approach and the mobile application approach.